FACTORS AFFECTING THE COMMUNITY IN CONSUMING SPICERY PRODUCTS (JAMU) POST-PANDEMIC - Melyana Febryantari Wardana; Nikmatul Khoiriyah; Titis Surya Maha Rianti (Socio-Economics/Agribusiness Department, 2023)
Spicery products (jamu) can boost the body's immune system because of their properties. It causes the demand for herbal medicine to increase during the pandemic. The study aimed to analyze the factors influencing the public to consume post-pandemic spicery products (jamu). Researchers conducted research in the city of Malang. The sample was selected using the convenience sampling method with 100 respondents. This type of data uses primary data obtained from questionnaires. The questionnaire was assessed using a likert score and then analyzed using multiple linear regression. The results obtained, the value of Adjusted R Square (R2) is 88.5%, then all variables can explain the influence on consumption decisions on spicery products (jamu). Factors that have a significant effect include income (x1), social class (x3), motivation (x5), location (x8), time (x9), scent (x12), texture (x13), and price (x14). In contrast, the factors that have no significant effect include work variables (x2), tradition (x4), perception (x6), health (x7), shape (x10), and taste (x11). Knowing these factors will produce recommendations for producers to increase their sales, especially in implementing product marketing strategies.